Granular subbase resistance variation with the variation of plastic fines content in controlled gradations - Vega Quirós, Mónica (2025)
Pavement road surfaces wear down due to loading and weather conditions; lower layers (base, subbase and subgrade) conditions and characteristics also influence the structure performance. Influence of plastic fines content may also affect pavement structure deformability and should be a factor to take into account on base and subbase layers. This work quantifies the resistance variation of a subbase material, to propose a potentially feasible range of fine particles content usable in pavement designs. Determination of resistance were obtained by California Bearing Ratio (CBR) and Resilient Modulus laboratory tests, comparing different gradation subbases according to type of fines (plastic or non-plastic) and content of fines (4% - 12%). On subbases with plastic fines, effectiveness of lime as a stabilization additive was evaluated. Obtained results show that in cases when plastic fine particles in subbases are substituted by non-plastic fines, resistance is increased. Furthermore, when subbase plastic fines content is high, stabilization with lime produce a positive effect on increasing material's resistance.